Control strategy for modified CI-based Bi-directional Γ-Z source DC-DC converter for buck-boost operation - Remala Geshma Kumari; A Ezhilarasi; Naresh Pasula (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper introduces a novel Bi-directional coupled-inductor (CI) based Γ-Z source converter for step up-step down DC application. It is a modified version of CI based Γ-Z high gain converter. The converter originates under the family of impedance networks with two winding coupled inductor. The said converter when operated with low duty ratio makes converter to achieve high gain compared to conventional DC-DC converters. As the society is in trend with electric vehicles (EV’s) are recommending operating the converters in Bi-directional mode to have continuous power flow when those are operated with green technologies. So, the same converter is initially operated and verified as buck and boost converter in open loop mode. Nearly 38 and 4 voltage-gainin boost and buck mode was observed when realized in MATLAB environment for the designed inductor and capacitor values with 49% and 1% duty cycle respectively under open-loop configuration. In the succeeding a PID controller based closed loop control strategy has implemented for the same converter. Gain sensitivity of the converter had been verified in MATLAB Simulink environment. Results obtained from simulation and mathematical found satisfactory in open and closed loop.